ANALISIS HUBUNGAN KEPEMIMPINAN MELAYANI DENGAN KOMITMEN ORGANISASIONAL STUDI PADA BPJS KESEHATAN KANTOR WILAYAH JAMBI - Suyadi Suyadi (Jurnal Media Ekonomi (JURMEK), 2016)
To analyze the relationship between serving leadership (respecting others, developing others, building communities, displaying authority, giving leadership, distributing leadership) and organizational commitment to BPJS Health Office of Wialyah Jambi. Six hypotheses were tested in this study. 38 questionnaires were distributed to employees, 33 questionnaires that received a response rate or around 86%. The collected data were analyzed using validity analysis, reliability analysis, descriptive analysis, correlational analysis using SPSS 17. The results of the study showed that respecting other people was positively and significantly related to organizational commitment, which obtained the value of the correlation coefficient was 0.487. The results showed that developing other people was positively and significantly related to organizational commitment, which obtained a correlation coefficient value of 0.582. Thus building a community is positively and significantly related to organizational commitment, which is obtained by the value of the correlation coefficient is 0.606. While describing autensity is positively and significantly related to organizational commitment, which is obtained by the value of the correlation coefficient is 0.671. While to provide leadership is positively and significantly related to organizational commitment which obtained the value of the correlation coefficient is 0.639 and leadership distribution is positively and significantly related to the coefficient value correlation is 0.542.